Environmental and Health Risk Assessment of Fugitive Dust from Magnesium Slag Yards - Jing Hua; Yuanchao Zhao; Yuanzheng Zhang; Yining Zhu; Chang Liu; Fenghe Wang; Xiaowei Xu; Qi Yu (Toxics)
During the natural cooling process of magnesium slag stockpiles in the open air, the phase transformation of gamma-dicalcium silicate (γ-C2S) induces a powdering phenomenon, resulting in the generation of a large amount of PM10 and PM2.5 dust. Based on the dust emission model of stockpiles and the Gaussian dispersion model, combined with the Monte Carlo simulation method, this study conducted a quantitative assessment of the environmental risk of heavy metals (Pb, Cd, Hg, As, Cr(VI)) in dust to the surrounding residential areas. The results show that the enrichment degree of heavy metals in PM2.5 is significantly higher than that in PM10. At a downwind distance of 1000 m, the exceedance multiples of Cr(VI), As, and Cd reach 131.5, 23.6, and 51.8 times, respectively. The total carcinogenic risk (9.2 × 10−7) and total non-carcinogenic hazard quotient (0.15) in the residential area are below the limits, but the contribution rates of As and Cd are relatively high. Sensitivity analysis further reveals that the moisture content of the stockpile, dust removal rate, and distance are the key control parameters affecting the environmental risk. Based on the research findings, it is recommended to increase sprinkling frequency, install windbreak nets, and promote magnesium slag utilization to effectively control dust risks.